Assessment and evaluation of occupational stress among safety authorities: By possibility of cancer - Jaddi Madarsara, Tayyebeh; Yari, Saeed; Saeidabadi, Hamzeh (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: Protecting the workforce (the main factor in production entities) in the workplace is a top priority for any country. Therefore, the Ministry of Cooperation, Labor and Social Welfare, in order to achieve this and implement Article 85 of the Labor Code, has prepared and approved the bylaws on the use of safety officials in the workshops as liaison between industries and departments of Cooperation, Labor and Social Welfare, This confirms the special role of the safety authorities and, consequently, the job stresses of these industry workers. Methods: This descriptive-analytical study was conducted in 2017 with a population of 33 people (14 women and 19 men) from safety authorities working in Alborz industries with a working experience of 5.93±3.99. A 35-item questionnaire from the British Health and Safety Executive was used to investigate the factors affecting stress, it has a strong correlation between the 7 elements of the questionnaire (Role 0.92, relationship 0.73, authority support 0.75, coworker support 0.63, control 0.87, demand 0.85 and changes 0.22) and its Cronbach's alpha is 0.78. Results: By examining the frequency of questionnaire data in 7 identified areas, eight demand items (including expectations of different working groups, high workloads, lack of time to rest), two items of work relationship (tolerance of ugly words and misconduct, tension between colleagues), one manager support (working time constant) And one case of changes (stresses in work relationships) were stressful factors in the workplace. Conclusion: The results of this study showed that due to high workload and stress and workplace stressors, safety authorities have a great deal of work stress. and it is necessary to conduct training courses, familiarity with the requirements and rules of the workplace, control of false emotions, anger and stress management as well as identifying, evaluating and controlling the harmful factors and risks in the workplace to improve the workplace and reduce stress. it should be noted that with regard to the prevalence of breast cancer among women and 42.5% of the target group of women, the likelihood of work-related breast cancer is not out of the question.